Next-Generation Sequencing Analysis of ctDNA for the Detection of Glioma and Metastatic Brain Tumors in Adults - Liang, Jianfeng; Zhao, Wanni; Lu, Changyu; Liu, Danni; Li, Ping; Ye, Xun; Zhao, Yuanli; Zhang, Jing; Yang, Dong (Frontiers in Neurology, 2020)
Background: The next-generation sequencing (NGS) technologies related assessments of circulating tumor DNA (ctDNA) in both primary brain tumors and metastatic brain tumors are still rare. Methods: This retrospective, single-center study was performed based on a protocol approved by the institutional review board at Peking University International Hospital. Genomic DNA was extracted from blood samples or tumor tissues. Sequencing was performed on a NextSeq 500 instrument (Illumina) with an average coverage of 550-fold. Paired-end sequencing was employed to improve the sensitivity of duplicate detection and increase the reliability of detection of possible fusions. Results: A total of 27 patients (21 men and 6 women) with brain tumors were enrolled in this study and they were divided into two groups including primary brain tumor group (n=22) and metastatic brain tumor group (n=8). The mean age of metastatic brain tumor group (61.2±9.4 y) was significantly higher than the mean age of primary brain tumor group (45.3±12.3 y) (P<0.05). The mutant genes in this group included ALK, MDM2, ATM, BRCA1, FGFR1, KRAS, however, there was no glioma-related mutant genes including MGMT, IDH1, IDH2, 1p/19q, BRAF. The characterizations of IDH mutations in the glioma included IDH1 mutation (p.R132H) and IDH2 mutation (p.R172K). The mutation abundance of IDH in tumor tissues was 37.06±8.32% which was significantly higher than that in blood samples (P<0.05). Conclusion: The mutant genes between primary and metastatic brain tumors are different. The mutant genes in the metastatic brain tumors included ALK, MDM2, ATM, BRCA1, FGFR1, KRAS, and glioma-related mutant genes included MGMT followed by frequencies of IDH1, 1p/19q, BRAF and IDH2.